2022
DOI: 10.1093/femsec/fiac022
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the phyllosphere and rhizosphere microbial communities of soybean in the presence of pathogens

Abstract: Soybean (Glycine max L.) is host to an array of foliar- and root-infecting pathogens that can cause significant yield losses. To provide insights into the roles of microorganisms in disease development, we evaluated the bacterial and fungal communities associated with the soybean rhizosphere and phyllosphere. For this, leaf and soil samples of healthy, Phytophthora sojae-infected and Septoria glycines-infected plants were sampled at three stages during the production cycle, and then subjected to 16S and ITS am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 114 publications
1
11
0
Order By: Relevance
“…In recent years, several publications have reported that pathogen infections may result in changes to the microbiome in many pathosystems ( 33 , 58 , 59 ). In this study, we observed a higher alpha diversity of bacterial communities than that of fungal communities, and similarly, an elevated bacterial alpha diversity was observed in Arabidopsis root and soybean rhizosphere systems in previous studies ( 60 , 61 ). Notably, we observed that the alpha diversity of both bacterial and fungal communities in healthy Kelsey leaves increased progressively from the first to the fifth stage, with a slight decrease in the sixth stage; this suggests a potential mechanism by which the highly diverse microbial communities in healthy leaves can trigger increasingly intensive interactions with the plant immune systems to avoid pathogens ( 62 ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In recent years, several publications have reported that pathogen infections may result in changes to the microbiome in many pathosystems ( 33 , 58 , 59 ). In this study, we observed a higher alpha diversity of bacterial communities than that of fungal communities, and similarly, an elevated bacterial alpha diversity was observed in Arabidopsis root and soybean rhizosphere systems in previous studies ( 60 , 61 ). Notably, we observed that the alpha diversity of both bacterial and fungal communities in healthy Kelsey leaves increased progressively from the first to the fifth stage, with a slight decrease in the sixth stage; this suggests a potential mechanism by which the highly diverse microbial communities in healthy leaves can trigger increasingly intensive interactions with the plant immune systems to avoid pathogens ( 62 ).…”
Section: Discussionsupporting
confidence: 89%
“…For the phyllosphere fungal community, we found that Diaporthaceae and Didymellaceae were significantly enriched in the sixth stage of G. yamadae -infected leaves. Diaporthe and Didymella are major pathogenic members of the families Diaporthaceae and Didymellaceae , respectively, which have been significantly enriched in diseased plant roots in previous studies ( 61 , 70 ). Therefore, these fungal groups may be opportunistic pathogens that colonize highly vulnerable diseased plants ( 61 ).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Rhizobiomes dominated by Pseudomonadaceae , Bacillaceae , Solibacteraceae and Cytophagaceae were realized for Fusarium oxysporum ‐resistant varieties of common bean (Mendes et al, 2018), whilst approximately 20 rhizosphere‐dwelling taxa were correlated with the prevalence of Fusarium virguliforme in soybean (Srour et al, 2017). Recently, Díaz‐Cruz and Cassone (2022) profiled fungal and prokaryotic communities in the soybean rhizosphere and phyllosphere upon infection with P . sojae and Septoria glycines .…”
Section: Emergent Strategies For the Management Of P Sojaementioning
confidence: 99%
“…sojae and Septoria glycines . For both plant compartments, alpha diversity indices were influenced negligibly by the presence of pathogens, although community structure and composition were affected considerably (Díaz‐Cruz & Cassone, 2022). The defined study is the first to correlate microbial dynamics in the soybean rhizosphere with P .…”
Section: Emergent Strategies For the Management Of P Sojaementioning
confidence: 99%